1999
DOI: 10.1093/oxfordjournals.jbchem.a022255
|View full text |Cite
|
Sign up to set email alerts
|

 -Hydroxyisovalerylshikonin Inhibits the Cell Growth of Various Cancer Cell Lines and Induces Apoptosis in Leukemia HL-60 Cells through a Mechanism Different from Those of Fas and Etoposide

Abstract: beta-Hydroxyisovalerylshikonin (beta-HIVS), which was isolated from the plant, Lithospermium radix, inhibited the growth of various lines of cancer cells derived from human solid tumors at low concentrations between 10(-8) and 10(-6) M. When HL-60 cells were treated with 10(-6) M beta-HIVS for 3 h, characteristic features of apoptosis, such as DNA fragmentation, nuclear fragmentation, and activation of caspase-3-like activity, were observed. The most characteristic features of the effect of beta-HIVS were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 0 publications
3
56
0
Order By: Relevance
“…␤-Hydroxyisovalerylshikonin (␤-HIVS) was purified from the plant Lithospermium radix as described previously. 18 Dihydroethydium, also called hydroethydine (DE) and 2Ј,7Ј-dichlorodihydrofluorescein diacetate, also called 2Ј,7Ј-dichlorofluoresin diacetate (DCFH-DA), were from Molecular Probes (Eugenes, OR). PD98059 and SB203580 were obtained from New England BioLabs (Beverly, MA) and Calbiochem (LaJolla, CA), respectively.…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…␤-Hydroxyisovalerylshikonin (␤-HIVS) was purified from the plant Lithospermium radix as described previously. 18 Dihydroethydium, also called hydroethydine (DE) and 2Ј,7Ј-dichlorodihydrofluorescein diacetate, also called 2Ј,7Ј-dichlorofluoresin diacetate (DCFH-DA), were from Molecular Probes (Eugenes, OR). PD98059 and SB203580 were obtained from New England BioLabs (Beverly, MA) and Calbiochem (LaJolla, CA), respectively.…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…18,21 In brief, JNK was precipitated from an aliquot of cell lysate that contained 400 g of protein by mixing the lysate with recombinant GST-c-JUN(1-79) that had been conjugated to glutathione-Sepharose. The Sepharose beads were pelleted by brief centrifugation in a microcentrifuge, and the bound protein complexes were washed three times with N-(2-hydroxyethyl)piperazine-NЈ-2-ethane-sulfonic acid (HEPES) binding buffer (20 mM HEPES, pH 8.0, 20 mM MgCl 2 , 0.1 mM EDTA, 50 mM NaCl, 0.05% Triton X-100).…”
Section: Assay Of Map Kinase Activitiesmentioning
confidence: 99%
“…The importance of apoptosis has been emphasized by recent demonstrations that various chemotherapeutic anti-cancer agents, such as cisplatin (Kaufmann, 1989;Barry et al, 1990;Evans and Dive, 1993), adriamycin (Friesen et al, 1996), and taxol (Bhalla et al, 1993), induce apoptosis in cancer cells. We have identified several differentiationor apoptosis-inducing compounds (Sakai et al, 1993(Sakai et al, , 1994Ohizumi et al, 1995;Masuda et al, 1995Masuda et al, , 1997Watabe et al, 1996) and found recently that bhydroxyisovalerylshikonin (b-HIVS) has potent apoptosis-inducing activity (Hashimoto et al, 1999). We isolated b-HIVS from a Chinese plant, Lithospermum erythrorhizon, and found that it had the strongest apoptosis-inducing activity of a variety of derivatives of shikonin in HL60 cells (Hashimoto et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We have identified several differentiationor apoptosis-inducing compounds (Sakai et al, 1993(Sakai et al, , 1994Ohizumi et al, 1995;Masuda et al, 1995Masuda et al, , 1997Watabe et al, 1996) and found recently that bhydroxyisovalerylshikonin (b-HIVS) has potent apoptosis-inducing activity (Hashimoto et al, 1999). We isolated b-HIVS from a Chinese plant, Lithospermum erythrorhizon, and found that it had the strongest apoptosis-inducing activity of a variety of derivatives of shikonin in HL60 cells (Hashimoto et al, 1999). In the present study, we tried to identify the gene that is involved in b-HIVS-induced apoptosis to clarify the molecular mechanisms of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…37,38) Shikonin has been reported to confer many medicinal properties such as anti-inflammatory and anti-tumor effects. 2,39) we therefore assumed that the effects of LR in this study would be related to shikonin or its derivatives.…”
Section: Discussionmentioning
confidence: 99%